2020
DOI: 10.2346/tire.18.460408
|View full text |Cite
|
Sign up to set email alerts
|

Compounding and Mixing Methodology for Good Performance of EPDM in Tire Sidewalls

Abstract: Ethylene propylene diene terpolymer (EPDM), which is a terpolymer of ethylene, propylene, and a diene, is characterized by having a fully saturated polymer backbone, resulting in excellent ozone and oxidative aging resistance. By contrast, diene elastomers such as natural rubber (NR) and polybutadiene rubber (BR) have high levels of unsaturation along their main polymer backbones, increasing their susceptibility to chemical degradation by main chain scission and therefore their need for a protection system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Most of these PPDs could be applied to the rubber products for the manufacturing of vehicle tires. For example, 6PPD is widely employed in commercial vehicle tire formulations (1–4% by mass). Several other PPDs, such as CPPD, IPPD, and DNPD, also find applications in rubber for tire manufacturing . Tire wear particles, which are formed from tires undergoing friction on the road, could be the primary route for the release of these rubber additives into the environment .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these PPDs could be applied to the rubber products for the manufacturing of vehicle tires. For example, 6PPD is widely employed in commercial vehicle tire formulations (1–4% by mass). Several other PPDs, such as CPPD, IPPD, and DNPD, also find applications in rubber for tire manufacturing . Tire wear particles, which are formed from tires undergoing friction on the road, could be the primary route for the release of these rubber additives into the environment .…”
Section: Resultsmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.est.2c07652. Physicochemical properties as well as overall persistence and long-range transport potential (Pov, CTD, and TE) of seven PPDs and four PPD-Qs (Table S1); optimized ESI (+)-MS/MS parameters (Table S2); summarized QA/QC results (Table S3); detailed concentration data (Table S4); Spearman's correlation analysis (Table S5); MRM chromatograms and MS 2…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
“…p -Phenylenediamines (PPDs) are an important class of synthetic antioxidants that are used as additives in rubber-related products, mostly in rubber tires. , Among the globally used PPDs, N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine (6PPD) is the most frequently used tire antioxidant and has been listed as a high production volume (HPV) chemical by the Organization for Economic Co-operation and Development (OECD) . In China, the current annual production of 6PPD alone is 200,000 tons, accounting for approximately 54% of the total production of all current-use rubber antioxidants .…”
Section: Introductionmentioning
confidence: 99%
“…Substituted para -phenylenediamines (PPDs), as a class of anthropogenic antioxidants, have been largely produced and applied in the rubber industry due to their capability for the protection of rubber materials against flex cracking, heat degradation, and ozone cracking. 1 However, massive production and consumption of these PPD antioxidants have caused increasing concern regarding their emissions and potential influence on the aquatic and terrestrial ecosystems. Emerged evidence indicated that these chemicals can be ubiquitously detected in receiving waters, 2 , 3 dusts, 4 , 5 sediments, 6 and air particles.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, N-isopropyl-m′-phenyl-p-phenylenediamine (IPPD) was defined as predominantly occupational allergens, causing allergic contact dermatitis through direct contact with industrial rubber. 11 A test report from the U.S. EPA has illustrated the acute toxicity of N,N′-bis (1,4-dimethylpentyl)-p-phenylenediamine (77PD) to rats through inhalation with a LC 50 of 400 mg/m 3 . 12 In addition to PPDs, the environmental emissions and acute toxicity of their derived quinones (PPD-Qs) have attracted great attention lately.…”
Section: ■ Introductionmentioning
confidence: 99%